TAREKAT JUNAIDIYAH DI KALIMANTAN SELATAN - Nor Ipansyah (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2011)
The name of AlphaJunaidiyah Tarekat attributed to the Sufi Abu al-Qasim Junaid al-Baghdadi. This Tarekat has a special attraction for its followers; those are the practical deeds, not exclusive and highly compromised with the situation of modern life. Historically this Tarekat has included the oldest Tarekat in the Islamic world, but its new entrants and developing in Indonesia, about 1956. This Tarekat is open, accepting students from various backgrounds and give them freedom to follow another tarekat. The genealogy of Junaidiyah Tarekat is not continued, but by his followers accepted the validity of the argument berzakhi theory or Uwaisy, which is commonly believed by the Sufis. The Junaidiyahs teachings or doctrines were sourced from the teachings of the books of Tawheed, Fiqh and Sufism is popular among Ahlussunah wal Jamaat. Implementation the teachings of Junaidiyah Tarekat was began with bai'at, granting diplomas and genealogy